Populist Radical Right Party-Voter Policy Representation in Western Europe. Issue 4 (2nd October 2019) - Backlund, Anders; Jungar, Ann-Cathrine
ABSTRACT: In this study we assess policy representation by populist radical right (PRR) parties in ten West European countries. Going beyond aggregate left-right or socio-cultural (GAL-TAN) dimensions of political conflict, we study representation on policy issues related to the PRR parties' core ideological features nativism, populism, and authoritarianism . Analysing data from party expert and voter surveys, we find that the PRR parties provide largely unique policy positions that are congruent with their voters' preferences in terms of their opposition to immigration and the European Union. By contrast, the parties are less representative in terms of their value conservative and authoritarian positions on gay rights and civil liberties. The findings have relevance for our understanding of party strategy, voter behaviour, and the dimensionality of political competition.